The European Green Deal – challenges for agriculture and the agri-food sector - Jarosz, Zuzanna (Polish Journal of Agronomy, 2023)
Growing climate and environmental problems obligethe search for efficient business solutions. In December 2019, theEuropean Commission issued a communication on the EuropeanGreen Deal strategy, which set ambitious goals in the pursuit ofclimate neutrality in 2050.The presented study is based on a literature review and legalacts. It identifies the rationale behind the European Green Dealstrategy, its aims and objectives. It also presents the farm-to-forkstrategy, which is intended to contribute to a fair, healthy and environmentallyfriendly food system. The transformation will requirecommitted action from all actors in the food chain, includingagriculture and the agri-food sector. The challenges faced byagriculture and the food industry in achieving the objectives ofthe strategy have therefore been identified. An attempt was madeto answer the question of what actions should be initiated so thattheir implementation in agriculture and the agri-food sector contributesto improving the state of the environment and stabilizingthe climate. Great importance in this regard is attributed to theimplementation of mitigation practices.